Comparison of Mini Percutaneous Nephrolithotomy (Mini PCNL) and Retrograde Intrarenal Surgery (RIRS) for the Minimal Invasive Management of Lower Caliceal Stones - Coskun, Alper; Eryildirim, Bilal; Sarica, Kemal; Çamur, Emre; Can, Utku; Saglam, Erkin (Urology Journal, 2021)
Purpose: To evaluate the stone-free rates, quality of life, complications, use of fluoroscopy, analgesic requirements, a hospital stay following the management of lower calyceal with two different techniques (Mini Percutaneous Nephrolithotomy and Retrograde Intrarenal Surgery) in a prospective manner. Material and Methods: 50 patients with a diagnosis lower pole 1-2 cm stone were included into the study and were randomized into two groups.(Mini PCNL n: 25) ( RIRS n: 25). Safety and efficacy of both methods along with some other certain related factors were comparatively evaluated in both groups. Results: There was no significant difference between preoperative stone size, stone to skin distance, hemogram and creatinine values, need for analgesic drug, patients' replies to visual analog scale (VAS). The duration of both the hospital stay and the exposure to fluoroscopy, hematocrit decrease due to hemorrhage, complication rates were significantly higher in cases undergoing mini PCNL when compared to RIRS. Additionally, any significant difference was not observed with respect to the stone-free rates. Despite an increase in quality of life following the both type operations was noted; there was no significant difference in the quality of life between the patients in both groups. Conclusion: Our findings demonstrated that both surgical techniques are the feasible alternatives in the minimal invasive treatment of lower pole stones. Although there was no meaningful difference in stone-free rates between two groups; complications, use of fluoroscopy, bleeding and duration of hospital stay were noted to be significantly higher in cases treated with mini PCNL.